PELAKSANAAN UPAH MENGUPAH SIAK BONDO DI JORONG SUNGAI EMAS NAGARI SARUASO MENURUT TINJAUAN FIQH MUAMALAH - Hafiz Daffa; Farida Arianti (Jurnal Integrasi Ilmu Syariah (Jisrah), 2022)
Wali Jorong Sungai Emas assigned several people to work on irrigating the rice fields (siak Bondo). Siak Bondo will work in case of landslides, grass growing and other things. Siak Bondi improves water flow to prevent water from entering the rice fields. The selection of Siak Bondo was carried out by Jorong Wali only, while the community was not involved in it. Siak Bondo is given a salary of 2 liters of rice which is given after the rice harvest. The work done by Siak Bondo will certainly get wages from each of the community's rice fields in Jorong Sungai Emas. At the beginning of the contract, the community did not object to the wage system, but because the community did not always get the same harvest, some even experienced crop failure, the wages of two liters of rice that were issued became heavy for farmers. Many people complain about the wage system. This study wants to discuss wage practices against Siak Bondo from the perspective of Sharia Economic Law.